Mejoramiento genético. Mejoramiento de caracteres. Mayor fijación de N - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1986)
The selection criteria for N fixation at CIAT includes plant vigor, nodule no., mass at mid-flowering, acetylene reduction activity, total N, and grain yield of materials grown in sand culture and in field trials with mild N stress. The breeding program has yielded materials with improved N2-fixation; with a greater understanding of the associated plant characters, choice of parents to combine these different characters, and refinement of the selection criteria, more progress is likely. In addition to these studies, evaluations were conducted with 2 sets of Rhizobium strains for their ability to compete against native strains. The results of these trials are presented in table form. (CIAT)